The Critical Period Hypothesis: A Convenient Excuse or a Real Barier for Adult Language Learners? - Sari, Ambar (Lembaga Yasin AlSys, 2025)
Age holds a significant role in second language acquisition (SLA). Several research shows that the ability to learn a second language decreases when someome gets older. This study reviewed relevant studies on the effect of age on second language acquisition in order to achieve the best results since language learning methods should be adapted to the learner’s age level and specific needs. The results explained that younger learners are more adept at mastering a second language due to their brain's plasticity, which allows them to learn new information quickly. They can easily acquire the language’s grammar, vocabulary, and prnounciation through immersion and exposure. As learners age, their ability to learn a second language decreases. After adolescence, the brain becomes less plastic, and the acquisition of second language becomes more challenging. Research also pointed out that language also has a positive influences on a country’s economic development, as well as improving the international relations of local entrepreneurs. However, adult learners can still learn a second language, but it may take more their time and effort. Moreover, the learning strategies and motivation that learners applied in learning the second language also play an important role in second language acquisition (SLA). Beginners may not have a solid motivation to learn a second language, while adult learners may have a stronger motivation due to professional or personal reasons. Age is a crucial factor in second language acquisition, but it is not the only factor that determines the success of language use. The learner’s learning strategies, exposure, and motivation to the second language also play a significant role in the acquisition of a second language.